Effectiveness of blended learning implementation for algorithm and programming course - Yuricha, Yuricha; Phan, Irwan Kurnia (Jurnal Inovasi Teknologi Pendidikan, 2023)
Algorithm and programming is a prerequisite course at the beginning of the semester, which not only requires an understanding of the basic concepts but also how these concepts can be implemented using a programming language. However, 72% of students have never studied programming at all. This is a challenge for teachers to be able to achieve learning objectives. This study aims to describe the learning design using the Blended Learning model so that its effectiveness can be measured in increasing student understanding in algorithms and programming courses. This research is Classroom Action Research (CAR) with a one-group pre-test post-test design for seven cycles implementing Blended Learning. Through the Wilcoxon Signed Rank test, it was found that there is an average of 92% increase in student understanding from the pre-test to the post-test. Therefore, the application of Blended Learning needs to be done and provides mature readiness for students during face-to-face meetings and teachers can evaluate learning outcomes more quickly and determine the direction of further learning actions.